Non-pharmacological interventions for improving sleep in people living with HIV: a systematic narrative review - Meng Jingjing; Zheng Chunyuan; Wang Honghong; Wang Min; Välimäki Maritta (FRONTIERS MEDIA SA, 2025)
Background: Sleep disturbances are common in people living with Human Immunodeficiency Virus (HIV) and may lead to poor adherence to antiretroviral therapy and worsen HIV symptom severity. Due to the side effects of pharmacotherapy for sleep disturbances, there is more room for non-pharmacological interventions, but knowledge of how these non-pharmacological interventions have been used to improve sleep in people living with HIV (PLWH) is still missing.
Objective: To investigate the content of non-pharmacological interventions, sleep measurements, and the impact of these interventions on improving sleep in PLWH.
Methods: Following PRISMA guidelines, we conducted a systematic search on PubMed, EMBASE, Cochrane Central Registry of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature, Web of Science, China National Knowledge Infrastructure, Wanfang Data, and China Biology Medicine disc. Non-pharmacological interventions for improving sleep in PLWH were included, and study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal checklists. We performed a narrative approach to synthesize the data to better understand the details and complexity of the interventions.
Results: Fifteen experimental studies in three categories for improving sleep in PLWH were included finally, including psychological interventions (components of cognitive-behavioral therapy for insomnia or mindfulness-based cognitive therapy, n = 6), physical interventions (auricular plaster therapy, acupuncture, and exercise, n = 8), and elemental interventions (speed of processing training with transcranial direct current stimulation, n = 1). Wrist actigraphy, sleep diary, and self-reported scales were used to measure sleep. Psychological interventions and physical interventions were found to have short-term effects on HIV-related sleep disturbances.
Conclusions: Psychological and physical interventions of non-pharmacological interventions can potentially improve sleep in PLWH, and the combination of patient-reported outcomes and actigraphy devices can help measure sleep comprehensively. Future non-pharmacological interventions need to follow protocols with evidence-based dosing, contents, and measures to ensure their sustainable and significant effects.